Population aging the transformation of societies - Rowland, Donald T. (International Perspectives on Aging, 2012)
Population Aging: The Transformation of Societies presents an overview and international comparison of the causes, consequences and policy implications of one of the major processes of change in contemporary societies. It provides a foundation for understanding and reflecting on key demographic and social trends, together with related theoretical and policy frameworks that are important in explaining changes and designing informed responses. With particular reference to countries that have the oldest or largest aged populations, the book presents a synthesis of research on population aging, new analyses of trends and a discussion of the major social policy strategies.   Key topics include the new demography of aging, population health, family change, the Third Age, international policy concepts and strategies, and comparisons of countries - such as in terms of the relative risks they face from population aging and their resilience as changes occur. Overall, the book presents a broad interdisciplinary perspective on the determinants and consequences of population aging.   The book is written for an international audience of policy makers, educators and practitioners in health and welfare, together with students in the social sciences and health sciences. It provides an accessible and academically informed exposition of the field for people engaging with issues arising from population aging in their own country.